(untitled) (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to identify and analyze the appropriate strategies to increase consumers of Krispy Banana products in the snack business headquarters of Benkayan Regency. The approach used is descriptive qualitative, utilizing data collection techniques through observation, interviews, and documentation. The data analysis technique is carried out qualitatively with stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that effective strategies to attract consumer buying interest include: product innovation with flavors and toppings, attractive marketing, friendly service, and the use of social media as a means of advertising. SWOT analysis is used to develop marketing strategies, overcome weaknesses, exploit opportunities, and be exposed to business threats. The conclusion of this study shows that innovative and targeted marketing strategies can increase consumer appeal and loyalty to Crispy Banana products. This study is expected to be a reference for UMKM players to develop their businesses sustainably.